Writing Essay with Conservation Contained in Elementary School to Build Positive Character Education About Environment (Journal of Primary Education, 2019)
Writing is important in the character education of elementary school students. The character education of conservation consists of 11 values, namely religious, honest, intelligent, fair, responsible, caring, tolerant, democratic, polite, tough, and loving the country. The love of the country is meant to love the culture and natural environment around us. Therefore the environment is closely related to conservation education. The observations indicate that in the writing of fourth grade elementary school students the character values of conservation have not showed. This attracts researchers to study more about the implementation of conservation contained of writing learning. The purpose of this study was to find the implementation of writing learning with conservation contents in the character education of fourth grade elementary school students. This research is a descriptive qualitative study. This research was carried out at SD Muhammadiyah (SD M) and SDIT Logaritma (SD L) in Karanganyar, Kebumen.The data collection techniques used was in-depth interviews, observations, and documentation. The results of the study showed that the implementation of learning writing with conservation content is focused on the activities of initiating the learning, activities of managing the learning, and activities of closing the learning activities. In the activity of initiating the learning, all of the fourth grade teachers of Islamic Elementary School in Karanganyar have conditioned students, performed apperception, conveyed goals, provided motivation, and informed the learning activities to be carried out. In the learning management activities, the fourth grade teacher of Islamic Elementary School in Karanganyar did not fully teach in accordance with the Learning Implementation Plan. At the end of the learning activities include concluding the learning that has been done, checking the understanding of students, giving questions about evaluating or giving assignments, and closing the learning with prayer. The conservation character that emerges in the activity of initiating the learning was religious. The activity of managing learning raises honest, intelligent, responsible, tolerant, democratic and polite characters. The activity of closing the learning raises honest, responsible and religious characters.